Buffaloes Production and Reproduction Efficiencies as Reviewed for Parity in Nepal - Lamsal, Sadikshya; Subedi, Deepak; Kaphle, Krishna (International Journal of Applied Sciences and Biotechnology, 2020)
Buffalo rearing is major part of Nepalese agriculture and they are reared for milk, meat, draft power and manure. Buffaloes are the main source of milk production in Nepal producing about 65.3% of the total annual milk in the country. Different indigenous breeds such as Lime, Parkote and Gaddi as well as Indian Murrah and Nili Ravi are recorded in Nepal and they are raised in different management and production system. Different genetic and non-genetic factors cause variation in production and reproduction performance between these breeds and within these breeds also. Non genetic factors affecting the performance of these buffaloes are season of calving, parity, management practices, nutrition etc. In this paper, effect of parity on production traits such as colostrum period, lactation length, lactation yield and days to reach peak milk yield as well as reproduction traits such as calving interval, dry period and service period are reviewed. Thus, this paper after reviewing related articles from various journals, proceedings and magazines is aimed to evaluate the effect of parity on reproductive and production efficiency of buffaloes of Nepal. Though the performance of indigenous breed is generally considered low, there is high potential of these breeds under proper breeding and management programs. Int. J. Appl. Sci. Biotechnol. Vol 8(1): 1-6.